PEMBAKUAN PERISTILAHAN PERKOMPUTERAN DALAM BAHASA INDONESIA - tri indah kusumawati (NIZHAMIYAH, 2017)
Indonesian language standardization that has been done by the government in the form of appropriate rules in spelling, vocabulary, grammar, and terminology. Standardized Indonesian language guidance in the form of an (EYD), General Terms of Establishment, Standard Indonesian Grammar, and Big Indonesian Dictionary (KBBI). These guidelines serve as a reference for selecting the correct language form. Tips for Standardization of Indonesian Computing Terminals which contains Practical Guide for Establishment of Computer Terms, Special Guidelines for the Use of Computer Terms and the List of Indonesian Computer Terms is one of the means issued by the Implementing Team of Presidential Instruction No. 2 Year 2001 for use, either by users or developers of the computer.